The teaching of science : 21st century perspectives - Bybee, Rodger W. (National Science Teachers Association, 2010)
What should citizens know, value, and be able to do in preparation for life and work in the 21st century? In The Teaching of Science: 21st-Century Perspectives, renowned educator Rodger Bybee provides the perfect opportunity for science teachers, administrators, curriculum developers, and science teacher educators to reflect on this question. He encourages readers to think about why they teach science and what is important to teach.